School Agricultural Learning Center for Sustainable Agricultural Learning - Wattana SADUAK; Pakkapong POUNGSUK; Ratchadakorn PHONPAKDEE; Sataporn DEEYING (My University, 2019)
Agricultural education based on active learning (learning by doing) is an essential part of the daily school life which may promote the acquisition of knowledge and skills related to the ecological and social dimensions of sustainability. The purpose of this study was to compare the learning achievements and skills in agricultural practices between students who learned through the School Agricultural Learning Center (SALC) and those who learned in the normal classroom. Participants were 150 Thai high school students in grade 12 recruited by purposive sampling. The study included three steps: 1) Investigation of basic data for developing the SALC, 2) Establishment and development of the SALC, and 3) Use of the SALC for learning: Facebook and Line were employed as the channels for knowledge exchange, communication on learning activities holding and activities transfer. A posttest-only control group design was employed. The results revealed that the students who learned through the SALC exhibited significantly (p < 0.01) higher learning achievements and skills in agricultural practices than those who learned in the normal classroom. Our findings suggest that the SALC is pivotal for improving the students’ learning achievements and skills in agriculture and should be promoted to become a natural part of sustainable agriculture education.
Keywords: Agricultural Education; Diverse Educational Innovations Studies